Integrated Study of New Faunal Assemblages Dominated by Gastropods at Three Vent Fields Along the Mid-Atlantic Ridge: Diversity, Structure, Composition and Trophic Interactions - Sarrazin, Jozée; Cathalot, Cécile; Laes, Agathe; Marticorena, Julien; Michel, Loïc N.; Matabos, Marjolaine (Frontiers in Marine Science, 2022)
To date, two main vent faunal assemblages have been described on active sulfide edifices along the northern Mid-Atlantic Ridge (nMAR): one dominated by bathymodiolin mussels in low temperature areas and the other dominated by alvinocaridid shrimp in warmer habitats. In this study, we describe the ecology of new types of assemblage, dominated by gastropods, that are recurrent in several nMAR vent fields, from ~830 m to 3500 m depth. We assessed and compared the composition, abundance, diversity and trophic niche of these assemblages from three vent fields (Menez Gwen, Lucky Strike and Snake Pit) and characterized their habitats in terms of key environmental conditions. These assemblages, first seen during the Momarsat cruise in 2012 at the Lucky Strike vent field, were investigated during several subsequent cruises. They appear to be widespread along the nMAR, forming two distinct assemblages, one dominated by Lepetodrilus atlanticusat the shallowest vent field Menez Gwen, and the other by Peltospira smaragdina at the other investigated fields. Our data seem to indicate that these gastropods dominate an intermediate habitat at MAR vents and may play an important ecological role in these communities.